Efektivitas Ombudsman dalam Pengawasan Maladministrasi : Analisis Peran dan Hambatan Struktural melalui Kajian Literatur - Dinda Aprilia Putri; Jumiati; Boni Saputra (CV. ITTC INDONESIA, 2025)
The Ombudsman of the Republic of Indonesia or ORI is an institution that oversees the implementation of public services in Indonesia. In addition to overseeing the implementation of public service, the Ombudsman aqlso functions to prevent and overcome maladministration in the implementation of public service. The Purpose of writing this article is to analyze the role and obstacles of the Ombudsman of the Republic of Indonesian in overcoming maladmistration in public service in Indonesia. The method used is a literature review. From several articles in journals and other sources, it was found that the role of the Ombudsman of the Republic of Indonesia in overcoming maladministration is to receive reports of alleged maladministration, examine reports, request clarification of reports, make and provide recommendations regarding the resolution of maladministration reports. Furthemore, the obstacles faced by the Ombudsman of the Republic of Indonesia in overcoming maladministration are two factors: internal factors; the Ombudsman lacks human resources, changes in positions in the Ombudsman, lack of funds. Meanwhile, external factors include people who are not familiar with Ombudsman of the Republic of Indonesia, people who feel it is useless report to Ombudsman of the Republic of Indonesia, lack of cooperation from reported agencies in providing clarification, many reported parties do not comply with summons, recommendations from Ombudsman of the Republic of Indonesia are not implemented by the reported, and there is no execution of samctions by the government against violations of public service.